Conversion Practices Legislation in Victoria: A Potential Crisis for Church Authority? - Rhett Martin (Australian Journal of Law & Religion)
The Victorian Change or Suppression (Conversion) Practices Prohibition Act 2021 (Vic) prohibits change and suppression practices that alter or fundamentally change someone’s sexual orientation or gender identity. Whilst the intent of the Act is worthy, the devil is very much in the detail, especially in how the Act includes religious and psychiatric practices and services in its potential ambit. The other contentious issue is the range of powers provided to the Victorian Equal Opportunity and Human Rights Commission, which some argue potentially blur the lines on separation of powers between the judiciary and the legislature. This paper argues some amendments to the Act may be required in order to address these issues.